Effect of a Novel Dietary Antioxidant on Growth Performance and Antioxidant Status of Nursery Pigs - Ron Aldwin S. Navales; Jamil Faccin; Mike D. Tokach; Izuru Shinzato; Joel M. DeRouchey; Katelyn N. Gaffield; Jordan T. Gebhardt; Robert D. Goodband; Theresa Rathbun; Jason C. Woodworth; Tsuyoshi Tonoue; Daisuke Matsui; et al. (Kansas Agricultural Experiment Station Research Reports, 2025)
To evaluate the effect of dietary S-ascisic acid (S-ABA) supplementation on the growth performance and antioxidant status of pigs, 320 nursery pigs (DNA 241 × 600; initially 12.0 ± 1.13 lb) were weaned at approximately 18 d of age and assigned to pens in a generalized randomized block design with gender and weight category as blocking factors. Pigs were fed a common phase 1 diet from weaning to d 7. On d 8 post-weaning, pen of pigs (14.2 ± 1.25 lb) within gender × weight blocks were randomly allotted to one of four dietary treatments. Treatments included a conventional nursery diet (Control) and three diets that used the Control formulation with increasing S-ABA (0.5, 1.0 and 5.0 ppm). Treatments were provided during phases 2 (d 0 to 14) and 3 (d 14 to 35). Growth performance was measured weekly. Additionally, 32 pigs on d 0 and two pigs per pen on d 14 and 35 were bled to assess the erythrocytes’ total glutathione (GSH+GSSG), reduced glutathione (GSH), oxidized to reduced glutathione ratio (GSSG:GSH), serum total antioxidant capacity (TAC), superoxide dismutase (SOD), and thiobarbituric acid reactive substances (TBARS). At the termination of the trial, two pigs in each pen were euthanized and duodenal, jejunal and ileal mucosa were collected to measure GSH+GSSG, GSH and GSSG:GSH. No interactive effect on growth performance between S-ABA and gender was observed throughout the study. Additionally, increasing S-ABA did not influence growth performance. There was also no interaction between S-ABA and collection day on antioxidant parameters. Erythrocyte GSH+GSSG tended to increase with higher S-ABA in the diet (linear, P = 0.056) on d 14, while GSH showed a similar trend at d 14 (linear, P = 0.096) and d 35 (quadratic, P = 0.100). The d 35 GSSG:GSH ratio decreased with increasing S-ABA in the diet (quadratic, P = 0.022). Serum TAC, SOD and TBARS were not influenced by S-ABA in the diet. Similarly, dietary S-ABA had no effect on GSH+GSSG, GSH and GSSG:GSH in the intestinal mucosa. In conclusion, supplementation of S-ABA in the diet improved the antioxidant status of nursery pigs by reducing the erythrocyte GSSG:GSH ratio without negative effects on growth performance.
Keywords: S-abscisic acid; antioxidant; glutathione; nursery pigs